Screening Zinc Protoporphyrin-Forming Lactic Acid Bacteria to Replace Nitrite in Meat Products - Qianhui Yang; Zhiqiang Feng; Qian Chen; Haotian Liu; Qian Liu; Fangda Sun; Baohua Kong (Foods)
Seventeen strains of LAB (lactic acid bacteria) were screened for their ability to form ZnPP (zinc protoporphyrin) by measuring fluorescence intensity. Three strains (Weissella viridescens JX11, Weissella viridescens MDJ8, and Lactobacillus pentosus Q) exhibited notable ZnPP-forming ability. The ferrochelatase enzyme activity of W. viridescens JX11 was significantly higher than that of the other two strains (p < 0.05). The three selected strains were then inoculated into minced meat to observe their effect on color development and quality properties. The a*-values of the bacteria-inoculated groups were significantly higher than those of the control group and lower than those of the nitrite group (p < 0.05). The visible bright red color of the inoculated groups was stronger than that of the control and inferior to the nitrite group, especially in cooked minced meat. The fluorescence intensities in inoculated groups were significantly higher than those of the control and nitrite groups (p < 0.05). The UV–Vis absorbance data at 417 nm indicated that inoculated groups exhibited higher absorbance compared to the control group (p < 0.05). These results indicate that high ZnPP-forming bacteria can enhance the color of meat products and these have certain potential to replace nitrite in meat products.